The impact of the Covid-19 pandemic on the tourist visits to Maribor in 2020 and 2021 - Horvat, Uroš (Journal for Geography, 2021)
The impact of the Covid-19 pandemic on the tourist visits to Maribor in 2020 and 2021The author notes that the number of tourist visits to Mariborbefore the pandemic increased significantly, and reaching a peak in 2018 with 466 thousand overnight stays and in 2019 with 218 thousand tourists. In 2020 and 2021, the tourist activity was subject to various restrictive measures taken at the global and national levels due to the Covid-19 pandemic, and tourist visits fell dramatically. The number of tourists in 2020 reached about 72 thousand, which was only 33% of the tourists from 2019 and was lower than before year 1964 and lower than in the period between 1991-2007. There was a slightly smaller decrease in the number of overnight stays,which in 2020 reached 43% of overnight stays from 2019. The decrease was mainly due to the decline in foreign tourist visits, especially from more distant countries and outside Europe. In 2020, most tourists visited Maribor from countries within a radius of about 300-700 km, from which mostly tourists came by car, as most of them decided on shorter and closer trips for safety reasons.
Keywords: Covid-19; pandemic; tourist visit; tourist development; tourists; overnight stays; average length of stay of tourists; Maribor; Slovenia